Satellite nodules in pleomorphic adenomas of the parotid gland: A nightmare for less invasive parotid surgery? - Iro, Ann Kristin; Agaimy, Abbas; Müller, Sarina Katrin; Sievert, Matti; Iro, Heinrich; Mantsopoulos, Konstantinos (Oral Oncology, 2021)
Objectives: The aim of this study was to thoroughly investigate the incidence of satellite nodules (SN) and some of their characteristics (number, distance to main lesion) in a large series of pleomorphic adenomas (PA) and to compare several surgical modalities regarding their efficacy in addressing this critical morphological feature. Materials and methods: The records of all patients treated for primary PA of the parotid gland between 2006 and 2020 were studied retrospectively. All the histological slides of all tumours were critically re-evaluated for this study by an experienced head and neck pathologist. Results: 845 cases made up our initial study sample. SNs were detected in 68/845 cases (8%). No statistically significant difference could be detected in the incidence of SNs in the surgical specimens between the patient groups managed by extracapsular dissection (46/577, 7.9%) and facial nerve dissecting surgery (22/268, 8.2%, p = 0.502). In the group of cases with SNs, no recurrences were detected (mean follow-up time: 71.4 months). The mean distance from the main lesion to the most distant SN was 1.1 mm (0.08–6.3 mm). The mean size of the SN was 1.9 mm (0.1–9.7 mm). Altogether, the mean distance from the main lesion to the outer periphery of the most distant SN was 3.1 mm (0.4–10.5 mm). Conclusion: Our analysis could not award SNs the title of an “extracapsular dissection's nightmare”. In the majority of cases, their favourable histological patterns offer the ideal circumstances for their surgical inclusion in a tumour specimen.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Capsule; Extracapsular dissection; Parotidectomy; Pleomorphic adenoma; Satellite nodule